Abundance decline in the avifauna of the European Union reveals cross‐continental similarities in biodiversity change. Issue 23 (15th November 2021) - Burns, Fiona; Eaton, Mark A.; Burfield, Ian J.; Klvaňová, Alena; Šilarová, Eva; Staneva, Anna; Gregory, Richard D.
Abstract: Although global assessments provide evidence of biodiversity decline, some have questioned the strength of the evidence, with local assemblage studies often showing a more balanced picture of biodiversity change. The multifaceted nature of biodiversity and imperfect monitoring datasets may partially explain these findings. Here, using an extensive dataset, we find significant biodiversity loss in the native avifauna of the European Union (EU). We estimate a decline of 17–19% in the overall breeding bird abundance since 1980: a loss of 560–620 million individual birds. Both total and proportional declines in bird numbers are high among species associated with agricultural land. The distribution of species' population growth rates (ln) is centered close to zero, with numerical decline driven by substantial losses in abundant species. Our work supports previous assessments indicating substantial recent biodiversity loss and calls to reduce the threat of extinctions and restore species' abundances, for the sake of nature and people. Abstract : Using an extensive high‐quality dataset, we estimate a decline of 17%–19% in overall native breeding bird abundance in the European Union since 1980: a loss of 560–620 million individual birds. The distribution of species' population growth rates (ln) is centred close to zero with numerical decline driven by substantial losses in abundant species. Our work supports previous assessments indicating recent biodiversity loss and calls to reduce the threat of extinctions and restore species' abundances, for the sake of nature and people.